Prevalence of Malnutrition Among Individuals with Down Syndrome in Zliten City: A Study of Relevant Factors - Al-Hashani, Hawwa Abdussalam; Al-Ati, Miftah Khaleel; Nouara, Abdulssalam Salem; Al-Kazaghli, Manal Gumah; Ermes, Fatima Melad; Abdewi, Karima Hussein (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Down syndrome (DS) is a type of disability that can affect quality of life and performance and create health and economic bur-dens in the community, particularly when associated with nutritional issues. The study aims to assess the nutritional status and related factors to highlight the malnutrition issue in this group. The study relied on the descriptive analytical approach, conducted on 38 individuals with DS (IDS) in Zliten City of both genders and aged 4-22 years. The data was obtained from their parents using a questionnaire tool, which included age, gender, family size, health problems, food habits that hinder eating, physical activity, and attitudes toward certain types of foods. Categorized study individuals were the three groups: children, adolescents, and adults. The calculated body mass index (BMI) to a known nutritional status. The data were analyzed using the correlation coefficient and T-test by SPSS program version 23 (2015). The results revealed that normal, overweight, and obesity represented 47.4, 21, and 31.6% respectively. The children group had the majority obese and 65.8% relied on self-feeding, 84.2% were not on a special diet and 78.9% had difficulty chewing and swallowing. Statistical analysis at P ±0.05 showed that family size had a significant effect on following a diet, increasing family members leads to less attention to diet, and other factors have no significance. Malnutrition is a prevalent problem in IDS. The family size and elevated percentage of not following a diet are determinants of malnutrition in the current study.